Vacancies, interstitials and close Frenkel Pairs on the zinc sublattice of ZnSe - DONEGAN, JOHN FRANCIS (American Physical Society, 1996)
Zinc vacancies (VZn), zinc interstitials (Zni), and ~25 distinct VZn?Zni Frenkel pairs of different lattice separations are observed in ZnSe by the optical detection of magnetic resonance in photoluminescence after 2.5 MeV electron irradiation in situ at 4.2 K. The stability, photoluminescence energy, anisotropy of production vs beam direction, plus exchange and dipole-dipole interactions in the excited emitting state are measured directly for most of the pairs. Combining this with information previously determined for the isolated vacancy and interstitial, the electronic and lattice structures of the defects and their role in the various luminescence processes are established. The second-donor level (+/2+) for Zni is estimated to be at EC-0.9 eV.
PUBLISHED
Keywords: Physics